أثر جودة التدقيق الداخلي في الحد من الاحتيال الإلكتروني في المحافظ المالية: دراسة تطبيقية على شركات الاتصالات الأردنية وتكنولوجيا المعلومات - قاسم احمد الدباس; نور علي الوشاح (جامعة الوادي University Of Eloued, 2024)
هدفت هذه الدراسة إلى التعرف على أثر جوده التدقيق الداخلي بأبعادها (الموضوعية والاستقلالية، وجودة أداء العمل، والمؤهلات والكفاءات، وبذل العناية المهنية) في الحد من الاحتيال الإلكتروني في المحافظ المالية الخاصة في شركات الاتصالات الأردنية وتكنولوجيا المعلومات. ولتحقيق أهداف الدراسة تم اتباع المنهج الوصفي التحليلي من خلال تصميم استبانة تهدف إلى قياس كل من جودة التدقيق الداخلي بأبعادها، والحد من الاحتيال الإلكتروني. وتكونت عينة الدراسة من عينة عشوائية تمثلت في (92) من موظفي التدقيق الداخلي العاملين في الدائرة المالية في كل من شركات الاتصالات الأردنية ، وتوصلت الدراسة إلى أن هناك درجة اتفاق قوية وإيجابية فيما يخص متغير جودة التدقيق الداخلي على المحافظ المالية في شركات الاتصالات وتكنولوجيا المعلومات بأبعادها المختلفة من وجهة نظر المشاركين. كما وأكدت النتائج أن هناك درجة اتفاق قوية وإيجابية فيما يخص قدرة شركات الاتصالات الأردنية على الحد من الاحتيال الإلكتروني من وجهة نظر المدققين الداخليين. وأوصت الدراسة ضرورة قيام شركات الاتصالات بدعم مهنة التدقيق الداخلي من قبل مجلس الإدارة مما يساهم في تعزيز دور المدقق الداخلي قي تخطي أهم التحديات التي تواجها مهنة التدقيق. This study aimed to identify the impact of internal audit quality with its dimensions (objectivity, independence, quality of work performance, qualifications and competencies, and exercise of professional care) on reducing electronic fraud in financial portfolios with its dimensions (electronic fraud related to employees, electronic fraud related to management, electronic fraud related to data Fraudulent financial, electronic fraud related to misappropriation of assets) at Jordanian telecommunications and information technology companies.To achieve the objectives of the study, the analytical descriptive approach followed by designing a questionnaire aimed at measuring both the quality of internal auditing and its dimensions, and the reduction of electronic fraud. The study sample consisted of a representative random sample of (92) employees in the financial department in each of the telecommunications and information technology companies.The study concluded that there is a strong and positive degree of agreement regarding the quality of internal auditing variable on financial portfolios at telecommunications and information technology companies with its different dimensions from the participants' point of view. The results also confirmed that there is a strong and positive degree of agreement regarding the ability of Jordanian telecommunications and information technology companies to reduce electronic fraud from the point of view of internal auditors. The study recommended the need for communications and information technology companies to support the internal audit profession by the Board of Directors, which contributes to strengthening the role of the internal auditor in overcoming the most important challenges facing the audit profession.
The Impact of Internal Audit Quality on Reducing Electronic Fraud in Financial Portfolios: An Applied Study on Jordanian Telecommunications Companies
Keywords: جودة التدقيق الداخلي; الاحتيال الإلكتروني; المحافظ المالية; شركات الاتصالات الاردنية وتكنولوجيا المعلومات; internal audit quality; electronic fraud; financial portfolios; communications and information technology companies